2019
DOI: 10.5248/134.119
|View full text |Cite
|
Sign up to set email alerts
|

Trichoglossum tetrasporum, newly recorded from India

Abstract: The uncommon earth tongue, Trichoglossum tetrasporum, is recorded for the first time from India. Macroscopic and microscopic characters of the species are described and illustrated along with its world distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The present study revealed that a total of 217 different morphotypes were collected from eight different districts of Tripura and 55 mushrooms were collected from West Tripura District, whereas previous findings (Debnath et al 2017) showed that West Tripura contained 22 morphotypes. There are few reports on mushrooms in Tripura (Debnath et al 2017(Debnath et al , 2019(Debnath et al , 2020a) but a study on mushroom diversity of the state of Tripua has not been conducted earlier. Baptista et al (2010) recorded a total of 2677 carpophores belonging to 73 species across 16 families and 23 genera in the Tra´s-os-Montes region of Northeast Portugal, which also showed more or less dissimilarity with our finding.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that a total of 217 different morphotypes were collected from eight different districts of Tripura and 55 mushrooms were collected from West Tripura District, whereas previous findings (Debnath et al 2017) showed that West Tripura contained 22 morphotypes. There are few reports on mushrooms in Tripura (Debnath et al 2017(Debnath et al , 2019(Debnath et al , 2020a) but a study on mushroom diversity of the state of Tripua has not been conducted earlier. Baptista et al (2010) recorded a total of 2677 carpophores belonging to 73 species across 16 families and 23 genera in the Tra´s-os-Montes region of Northeast Portugal, which also showed more or less dissimilarity with our finding.…”
Section: Discussionmentioning
confidence: 99%